2014
DOI: 10.1016/j.drugalcdep.2013.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Concordance between self-reported substance use and toxicology among HIV-infected and uninfected at risk youth

Abstract: Background Substance use by youth living with HIV (YLWH) is a concern, given potential interactions with virus-associated immune suppression and adverse effects on risk behaviors, neurocognition, and adherence. Self-report substance use measures provide efficient cost-effective assessments. Analyses describe self-reported substance use among YLWH and examine agreement with toxicology assays. Methods Seventy-eight youth age 18–24 years (87% male, 71% African–American) with behaviorally acquired HIV-1 infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
3
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 28 publications
4
34
3
1
Order By: Relevance
“…In this sample of YLWH, we found a high incidence of STI diagnoses with estimates similar to those found in samples of adults living with HIV 21. Routine STI screening has been recommended for all sexually active individuals, including adolescents,18 21 23 and has been implemented in many HIV clinics in the USA.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In this sample of YLWH, we found a high incidence of STI diagnoses with estimates similar to those found in samples of adults living with HIV 21. Routine STI screening has been recommended for all sexually active individuals, including adolescents,18 21 23 and has been implemented in many HIV clinics in the USA.…”
Section: Discussionsupporting
confidence: 70%
“…Although ACASI technology was used to reduce social desirability bias, substance use data were based on self-report and there may be social desirability and recall bias. However, previous studies have found strong associations between self-report and substance use 21. We were only able to collect substance use information at one time point, which limits our ability to determine whether substance use is causally related to STI diagnoses.…”
Section: Limitationsmentioning
confidence: 94%
“…Although the majority of data were collected via self-report, we used computer assisted self-interviews which have been demonstrated to increase the reliability and validity of self-report data [52]. One recent study in the ATN found that the use of computer assisted self-reporting of drug use had high rates of concordance with toxicology results in youth with HIV infection [53]. Our participants had at least one clinical care visit during the study period; youth with undiagnosed HIV infection or otherwise not engaged in the medical system are not represented in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study in the ATN found that the use of computer assisted self-reporting of drug use had high rates of concordance with toxicology results in youth with HIV infection. 46 Finally, all participants are currently receiving some type of medical or psychosocial care through adolescent medical care clinics. Thus, youth with HIV infection who are not engaged in the medical system are not represented in this sample.…”
Section: Discussionmentioning
confidence: 99%